A note on the connection problem of some special Painlevé V functions. Issue 5 (4th May 2017) - Long, Wen-Gao; Zeng, Zhao-Yun; Zhou, Jian-Rong
Abstract : As a new application of the method of 'uniform asymptotics' proposed by Bassom, Clarkson, Law and McLeod, we provide a simpler and more rigorous proof of the connection formulas of some special solutions of the fifth Painlevé equation, which were established earlier by Andreev and Kitaev.